1785 N.C. Sess. Laws 710 - (:unkn) unknown (My University, 1785)
Raised the minimum militia age to 18. Militiamen included "all freemen and indented servants" (but not servants for life, a/k/a slaves). Militiamen had to arm themselves with "a well fixed gun and cartouch-box, with nine charges of powder made into cartridges and sizeable bullets or swan-shot, and one spare flint, worm and picker.
Keywords: MILITIAS; REQUIRED POSSESSION